Tabletop support for collaborative design: an initial evaluation of IdeaSpace - Ioannou, Andri; Loizides, Fernando; Vasiliou, Christina; Zaphiris, Panayiotis; Parmaxi, Antigoni (My University, 2015)
Addressing design problems through collaboration is a complex task in whichknowledge creation and shared understandings come from the reflective conversa-tion around design and redesign of artefacts. In a classroom setting, collaborativedesign often involves hands-on manipulation of physical artefacts such as sketchesand story boards, in addition to digital artefacts such as wireframes, mockups andhigh-fidelity prototypes. With the increasing availability of interactive surfaces, suchas interactive tabletops, we now have the opportunity to provide further support forthese activities, particularly collaboration and reflective conversations around designproblems. In this manuscript, we present IdeaSpace, a tabletop application designedto support collaborative design and learning as a continuous and reflective processinvolving cycles of design and redesign. In the following section, we present rele-vant work from the computer-supported collaborative learning (CSCL) literature.Next, the design rational and functionality of IdeaSpace are described. Finally, out-comes from three pilot case studies are presented together with concluding remarksand directions for future work.
Keywords: Multi-touch interactive tables; Tabletops; Collaborative design; Collaborative learning; Refection